GAMBARAN MANAJEMEN OBAT INSTALASI FARMASI RUMAH SAKIT SETIA MITRA DI JAKARTA SELATAN TAHUN 2022 - Irene Carolita Maharani Putri (2023)
Drug management in the hospital is an important element in the overall managerial function of the hospital. Guaranteed availability of quality, useful, safe and affordable medicines and medical devices is a requirement that must be met by pharmaceutical installations in hospitals. This research was conducted to find out the description of drug management in hospital pharmacy installations in South Jakarta in 2022. This research was carried out using a qualitative method using in-depth interviews with hospital staff, especially in pharmacy installations, data analysis, and direct observation. This study shows that the management of drugs in one of the hospital pharmacy installations in South Jakarta has not gone well, this is indicated by the availability of drugs that have not been fulfilled properly as indicated by the purchase of CITO drugs at the nearest pharmacy and hospital, a total of 202 types of drugs in 2010. 2022. Causal elements consist of input elements (HR, budget, and facilities and infrastructure), process elements (planning, budgeting, procurement, maintenance, control, recording and reporting, as well as monitoring and evaluation). Therefore, this research is intended so that Setia Mitra Hospital can make improvements to drug management so as to increase the quality and quantity of drug availability.